Upaya Peningkatan Pengetahuan Melalui Penyuluh Peran Suami Sebagai Fasilitator Dalam Persiapan Proses Persalinan - Sumawati, Ni Made Risna; Susila, I Made Dwie Pradnya (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2021)
Pada tahun 1999 sampai tahun 2000 pemerintah Indonesia telah mencanangkan programÂ  SuamiÂ  Siaga yang bertujuan untuk meningkatkan peran serta suami. Program lain yang telah dicanangkan Pemerintah Indonesia adalah â€œMaking Pregnancy Saferâ€ dimana diharapkan partisipasi, pengetahuan dan keterlibatan suami dapat meningkat selama proses persalinan (Depkes RI, 2012). Kegiatan ini dilakukan dengan metode ceramah dan diskusi sehingga suami dapat memahami tentang pentingnya peran suami sebagai fasilitator. Pelaksanaan penyuluhan tentang upaya meningkatkan pengetahuan tentang pentingnya peran suami sebagai fasilitator dalam persiapan proses persalinan dilaksanankan pada pada suami yang mengantarkan ibu melakukan pemeriksaan kehamilan di BPM Ni Ketut Nuriasih. Suami diberikan lembar pre test tentang peran pendampingan yang diperlukan untuk menemani istri bersalin, kemudian suami diberikan leaflet dan dijelaskan peran yang seharusnya dilakukan nanti saat menemani istri bersalin. Pada tahap akhir suami kembali diberikan lembar post tes untuk mengukur tingkat pemahamannya. Hasilnya seluruh suami yang diberikan penjelasan tentang peran sebagai fasilitator dalam menemani istri bersalin seluruhnya mengerti, dibuktikan dengan adanya peningkatan pemahaman dari hasil pre test dan post test. Saran Bagi klinik klinik yang menangani persalinan sebaiknya dalam pemberian KIE persiapan persalinan suami juga diikut sertakan sehingga ibu dan suami semakin siap menghadapi proses persalinan.Keywords:Â Fasilitator; Penyuluhan; Peran Suami; PersalinanKnowledge Efforts Through Release About The Importance Of Husband Role As A Facilitator In Preparing The Labor ProcessAbstractSince 1999 to 2000 the Indonesian government had launched the Husband Alert program which aimed to increase the participation of husbands. Another program that has been launched by the Government of Indonesia is the "Making Pregnancy Safer" where it is expected that the participation, knowledge and involvement of the husband can increase during the birth process (MOH RI, 2012). But until now there are still many husbands who do not understand their role well. So it is necessary to make efforts to increase knowledge through counseling about the importance of the husband's role as a facilitator in the preparation of the labor process. Counseling about the importance of the husband's role as a facilitator in the preparation of the birth process is done by the lecture method using leaflet props. Evaluation was carried out before and after the provision of counseling material (pre and post test). Counseling was carried out for 15 days from 1 to 15 June 2018 to 28 husbands who took mothers to carry out ANC examinations. The results of the post-test showed 78.6% experienced an increase in knowledge about the importance of the husband's role as a facilitator while the other 21.4% did not experience an increase in knowledge about the importance of the husband's role as a facilitator. Increased knowledge about the importance of the husband's role as a facilitator in the preparation of the birth process is influenced by several factors. One of them is the age factor and level of education. Recommendations for clinics that handle childbirth, it should always be included in the provision of counseling preparation for childbirth by explaining the role that must be done so that mothers and husbands are more ready to face the labor process.Keywords: Counseling; Childbirth;Â Facilitator;Â Role of Husband.